2013
DOI: 10.1007/s11130-013-0348-y
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Glycemic Response to Corinthian Raisins in Healthy Subjects and in Type 2 Diabetes Mellitus Patients

Abstract: This study was designed to evaluate the metabolic response to Corinthian raisins in healthy and in patients with type 2 diabetes mellitus. Healthy subjects (n = 15) and diabetic patients (n = 15) received 74 g raisins or 50 g glucose as reference food. Blood samples were collected at time 0 (before the consumption) and 30, 60, 90, 120, 150 and 180 min after raisin or glucose consumption. There was no significant difference in baseline glucose and insulin between raisins and reference in both groups. The differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 16 publications
2
23
0
1
Order By: Relevance
“…When the GI was investigated in three different groups (sedentary, aerobically trained or pre-diabetic subjects), no significant differences were found among groups, even though the GI (55–69) it seemed moderate for aerobically trained adults, and low (GI, ≤55) for the other groups [ 110 ]. Kanellos and collaborators found a moderate GI of raisins in healthy and T2D subjects [ 111 ], whereas Esfahani et al found that raisins were low-GI and glycaemic load (GL) foods in healthy subjects [ 112 ]. Recently, researchers have found that even though the same available CHO content from raisins and glucose generated a similar postprandial response, raisins significantly modulated the levels of GIP, ghrelin and ghrelin/obestatin ratio, with important implications in terms of appetite regulation and overall insulin secretion [ 113 ].…”
Section: Human Clinical Trialsmentioning
confidence: 99%
“…When the GI was investigated in three different groups (sedentary, aerobically trained or pre-diabetic subjects), no significant differences were found among groups, even though the GI (55–69) it seemed moderate for aerobically trained adults, and low (GI, ≤55) for the other groups [ 110 ]. Kanellos and collaborators found a moderate GI of raisins in healthy and T2D subjects [ 111 ], whereas Esfahani et al found that raisins were low-GI and glycaemic load (GL) foods in healthy subjects [ 112 ]. Recently, researchers have found that even though the same available CHO content from raisins and glucose generated a similar postprandial response, raisins significantly modulated the levels of GIP, ghrelin and ghrelin/obestatin ratio, with important implications in terms of appetite regulation and overall insulin secretion [ 113 ].…”
Section: Human Clinical Trialsmentioning
confidence: 99%
“…Dried fruits show promising potential for blood glucose management. Previous trials conducted in individuals with and without diabetes have shown dried fruits (including dates, apricots, raisins, and sultanas) to have a low (≤55) to medium (56–69) glycemic index (GI) 1–7 and to have beneficial effects on postprandial glucose 3,6,811 and insulin 3,6,11 levels, as well as HbA 1c 8 compared to high GI foods (e.g., crackers, cookies, white bread, glucose solution). However, the effect of combining dried fruits with high GI foods has not been adequately addressed.…”
Section: Introductionmentioning
confidence: 99%
“…This increase persisted in both the sensitivity and per-protocol analyses. Dried fruits have a low to moderate glycaemic index, and the acute glycaemic response to carbohydrate-rich meals is attenuated by replacement of refined starches with dried fruits (46)(47)(48)(49)(50) . The lower postprandial glycaemic response is likely due to partial glucose replacement by fructose, which does not contribute substantially to blood glucose and may even stimulate hepatic glucose uptake (51) .…”
Section: Discussionmentioning
confidence: 99%